2018
DOI: 10.1002/asia.201800114
|View full text |Cite
|
Sign up to set email alerts
|

ZrMn Oxides for Aqueous‐Phase Ketonization of Acetic Acid: Effect of Crystal and Porosity

Abstract: Aqueous-phase ketonization of bio-based acetic acid is important to improve the conversion efficiency of biomass resources. In this study, ZrMn mixed oxides (ZrMnO ) with high aqueous-phase ketonization activity are synthetized through a carbonization/oxidation method (COM) and solvothermal method (STM). The results show that ZrMnO prepared by COM possesses tetragonal ZrO , and hausmannite Mn O is observed only at a high oxidation temperature of 750 °C. Low-temperature and long oxidation results in decreased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The isotherms of MC and MC-700H 2 in Figure a are classified as Type II according to IUPAC standard, indicating the macroporous structures of the materials . The Type H3 hysteresis loops at higher p/p 0 value show the plate-like particles with interparticle adsorption, , which confirms the ordered macropores of MC-700H 2 (Figure ). The pore size distribution of MC exhibits a wide distribution from 2 to 100 nm.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The isotherms of MC and MC-700H 2 in Figure a are classified as Type II according to IUPAC standard, indicating the macroporous structures of the materials . The Type H3 hysteresis loops at higher p/p 0 value show the plate-like particles with interparticle adsorption, , which confirms the ordered macropores of MC-700H 2 (Figure ). The pore size distribution of MC exhibits a wide distribution from 2 to 100 nm.…”
Section: Resultsmentioning
confidence: 73%
“…The peak of β-Mo 2 C (101) was fitted, and crystallite sizes were calculated through Debye−Scherrer equations. 22 X-ray photoelectron spectroscopy (XPS) analysis was performed on a Thermo Fisher Escalab 250Xi spectrometer with Mg Kα radiation. All binding energies were corrected using C 1s line of graphite at 284.4 eV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wu et al have reported on the effect of porosity and crystal morphology when studying the aqueous phase ketonization of acetic acid with ZrMnOx catalysts. [100] With Zr-O-Mn as proposed active sites, it was shown that increasing the oxidation temperature and time (up to 550 °C and 24 hours) during synthesis via a carbonization-oxidation method led to a higher amount of highly dispersed Mn 4+ into smaller ZrO2 catalyst crystals with a larger amount of exposed surface atoms. As a result, an accompanying increase in Lewis acidity had a positive effect on the ketonization performance of acetic acid in water at 340 °C and 190 bar.…”
Section: Catalyst Morphology Structure and Crystal Phasementioning
confidence: 99%
“…Amphoteric metal oxides, such as TiO 2 , ZrO 2 , and CeO 2 , have been widely studied for ketonization due to their potential high activity. The surface of these metal oxides exposes acid–base pairs that are required to catalyze the reaction. The base site (oxygen ion) abstracts α-H, while the acid site (metal cation) stabilizes the active intermediate and enables C–C coupling, and both are crucial for ketonization. , Although many intermediates have been proposed for the reaction on metal oxides, the β-ketoacid has now been generally accepted as the key intermediate for ketonization. , However, there has been no consensus on the dependence of the β-ketoacid intermediate formation on the initial adsorption configuration of carboxylic acid.…”
Section: Introductionmentioning
confidence: 99%